A novel targeted proteomics method for identification and relative quantitation of difference in nitration degree of OGDH between healthy and diabetic mouse. Issue 21 (November 2014) - Yu, Qing; Liu, Bin; Ruan, Dandan; Niu, Chao; Shen, Jiayi; Ni, Maowei; Cong, Weitao; Lu, Xianghong; Jin, Litai
<x xml:space="preserve">Abstract</x> For analysis of nitration modification of α oxoglutarate dehydrogenase (α‐OGDH) induced by diabetes, a targeted proteomics strategy was developed through the use of Skyline. All peptides containing Y and W of the target proteins were nitrated in silico and output to produce parallel reaction monitoring (PRM) or SRM method for nitration analysis. A nitrated casein mixture was used as standard protein to assess the feasibility of this method. The results demonstrated the availability of this strategy for nitration identification, and subsequently this method was used to analyze the nitration of α‐OGDH from myocardial tissue extracts of diabetic mouse. The PRM method was primarily generated by Skyline for identification of the actual nitrated peptides from all possible nitrated peptides of α‐OGDH due to the complexity of α‐OGDH. The PRM‐based data were analyzed by SEQUEST, and transitions of the identified nitrated peptides were used to develop an SRM method for relative quantitation of nitration degree. The nitration degree of α‐OGDH for diabetic mouse is higher than that for control mouse, indicating that α‐OGDH of the diabetic mouse suffered from more intense oxidative damage. We believe that this approach for obtaining information regarding nitration will facilitate the study of other PTMs in complex mixtures.